2017
DOI: 10.1016/j.kint.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Urine biomarkers of tubular injury do not improve on the clinical model predicting chronic kidney disease progression

Abstract: Few investigations have evaluated the incremental usefulness of tubular injury biomarkers for improved prediction of chronic kidney disease (CKD) progression. As such we measured urinary kidney injury molecule-1, neutrophil gelatinase-associated lipocalin, N-acetyl beta-D-glucosaminidase and liver fatty acid binding protein under highly standardized conditions among 2466 enrollees of the prospective Chronic Renal Insufficiency Cohort Study. Over 9433 person-years of follow-up, there were 581 cases of CKD progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 73 publications
1
77
1
1
Order By: Relevance
“…1,2 Although a variety of novel urinary biomarkers of tubular injury, including neutrophil gelatinase-associated lipocalin, kidney injury molecule-1, and renal liver-type fatty acid binding protein, have been proposed to improve the accuracy of predicting the development of CKD, they have not been found to improve predictive models of CKD based on traditional laboratory tests in adults. 8,9 …”
mentioning
confidence: 99%
“…1,2 Although a variety of novel urinary biomarkers of tubular injury, including neutrophil gelatinase-associated lipocalin, kidney injury molecule-1, and renal liver-type fatty acid binding protein, have been proposed to improve the accuracy of predicting the development of CKD, they have not been found to improve predictive models of CKD based on traditional laboratory tests in adults. 8,9 …”
mentioning
confidence: 99%
“…7 Previous studies have shown associations between biomarkers of tubular injury, such as NGAL and kidney injury molecule-1, and loss of kidney function in patients with CKD, but their clinical usefulness has been challenged. [26][27][28] In the prospective Chronic Renal Insufficiency Cohort Study of 2466 patients with CKD with various etiologies and at different CKD stages, neither kidney injury molecule-1 nor NGAL were independently associated with the rate of disease progression, and none of the biomarkers tested improved the risk prediction in comparison with a clinical model that included eGFR and the urinary albumin-to-creatinine ratio. 26 Additionally, suPAR, which has been recently shown to be associated with eGFR loss during a longer time period (i.e., 1337 days), did not predict short-term decline of eGFR in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports of both blood and urine biomarkers have shown correlations with acute or chronic kidney injury in the general population . Proteins such as albumin, kidney injury molecule‐1, neutrophil gelatinase‐associated lipocalin, and β‐2 microglobulin, are associated with future GFR deterioration, but mainly in patients with abnormal baseline renal function.…”
Section: Discussionmentioning
confidence: 99%